Parental Guidance in Democratic Parenting Patterns on the Development of Religious and Moral Values in 5-6 Year-Old Children at RA Hajjah Fauziah Binjai - Tantri, Febby Elya; Hasibuan, Rabitah Hanum (AS-SABIQUN, 2026)
Although moral degradation in early childhood has received growing concern, studies specifically examining parental guidance through democratic parenting to optimize children’s religious and moral development remain limited, despite the substantial implications of this issue for children’s moral formation. This study aims to analyze parents’ guidance strategies through a democratic parenting style in optimizing the development of religious and moral values in children aged 5–6 years. The study employed a descriptive qualitative approach with a case study design involving samples drawn from three family types. Data were collected through participatory observation, in-depth interviews, and documentation, and were analyzed using the Miles and Huberman model. The findings indicate that a democratic guidance strategy characterized by two-way communication, the application of logical sanctions, and spiritual role modeling is able to support children in achieving a very good level of development. The study concludes that the synergy between democratic parenting at home and the use of audio-visual media in schools constitutes the most effective means of fostering children’s religious character intrinsically in the digital era. These findings contribute theoretically to the literature on the importance of parental guidance within democratic parenting for early childhood and provide practical implications for schools and parents in implementing effective mentoring strategies to cultivate a moral generation. In addition, the study opens opportunities for further research on the forms of guidance that teachers and parents can employ in shaping early childhood character.